Peningkatan Kapasitas Manajemen Sumber Daya Manusia Di Era Digital Melalui Pelatihan Kalender Kerja Karyawan Pada UMKM Binaan Kabupaten Bengkulu Tengah - Darta, Effed; Hayadi, Ilsya; Aprisella, Rhienta; Syoraya, Indah (Jurnal Dehasen Untuk Negeri, 2025)
This Community Service (PKM) activity aims to improve the understanding and skills of SMEs fostered by the Cooperative and Small Business Office of Central Bengkulu Regency in human resource management (HRM) in the digital era, especially in preparing employee work calendars. The activity began with surveys and discussions with SME owners to identify their needs and challenges in HR management. Training covering both theory and practical use of digital work calendars was conducted to improve operational efficiency. The results showed a significant increase in participants' understanding and ability to compile and apply digital work calendars, which are expected to increase productivity and adaptation to technological developments.